2009
DOI: 10.1080/15332960903408476
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Role of Job Resources in Mitigating Customer-Related Social Stressors and Emotional Exhaustion

Abstract: The effects of job resources on customer-related social stressors and emotional exhaustion, including the relationships of these stressors with emotional exhaustion, are tested with a sample of frontline bank employees in Northern Cyprus. The results provide empirical support for the majority of the hypotheses. Specifically, the results suggest that supervisor support has significant negative impacts on customer verbal aggression, disliked customers, and ambiguous customer expectations. The results further sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Turnover intentions were measured via a three-item scale taken from Singh, Verbeke, and Rhoads (1996). Using these items to measure study variables is congruent with past empirical studies (e.g., Karatepe et al, 2010;Kim et al, 2009). …”
Section: Measurementmentioning
confidence: 97%
See 3 more Smart Citations
“…Turnover intentions were measured via a three-item scale taken from Singh, Verbeke, and Rhoads (1996). Using these items to measure study variables is congruent with past empirical studies (e.g., Karatepe et al, 2010;Kim et al, 2009). …”
Section: Measurementmentioning
confidence: 97%
“…DCE refers to customers' service expectations that are evaluated as unjustified and sometimes unfair by frontline employees (Dormann & Zapf, 2004). CVA is associated with verbal abuse such as insults and yelling and hostile behaviours displayed at any time (Karatepe et al, 2010). DC is related to hostile, humourless, and unpleasant customers who do not respect frontline employees' work rhythm (Dormann & Zapf, 2004).…”
Section: Research Model and Hypotheses 21 Research Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Grandy (2007) suggests that verbal violations from outside, such as from customers, colleagues or superiors, have an impact on customer sentiment [8]. Results from Karatepe (2010) showed that social pressure from customers will make employees feel emotional exhaustion [9]. In the process of service exchanges, customer misconduct will make employees feel depressed.…”
Section: The Relationship Between Customer Misbehavior and Emotional mentioning
confidence: 99%